2019
DOI: 10.1080/20786190.2019.1596666
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of South African primary care: a cross-sectional descriptive survey

Abstract: In 2018 governments reaffirmed their commitment to implementing primary health care (PHC) in the Astana Declaration. South Africa has introduced a number of health reforms to strengthen PHC and enable universal health coverage (UHC). UHC requires access to quality primary care and progress needs to be measured. This study aimed to evaluate the quality of South African primary care using the Primary Care Assessment Tool (PCAT). Methods: A descriptive cross-sectional survey used data derived from a previous anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 11 publications
2
39
0
Order By: Relevance
“…The databases search yielded 5215 peer-reviewed studies (figure 1). At this stage a newly published study24 not yet indexed in Medline was added; it met the HR-1 rating. All titles were screened; abstracts of titles that screened positive or uncertain were examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The databases search yielded 5215 peer-reviewed studies (figure 1). At this stage a newly published study24 not yet indexed in Medline was added; it met the HR-1 rating. All titles were screened; abstracts of titles that screened positive or uncertain were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies24–36 addressed eight nationally validated PC performance instruments—namely the South African and Malawian versions of the Primary Care Assessment Tool (ZA PCAT and PCAT-Mw respectively)26 34; the electronic Tool to Improve Quality of Healthcare (e-TIQH) in Tanzania25; the Nigerian Patient Evaluation Scale (PES)31; the South African Ideal Clinic Realisation and Maintenance (ICRM) instrument29; SafeCare Essentials tool33; the European Task Force for Patient Evaluation of General Practice (EUROPEP)37; and the Client Satisfaction Survey Questionnaire 35. (Information on instruments is summarised in Appendix D uploaded as a supplementary file.)…”
Section: Resultsmentioning
confidence: 99%
“…14 Although not noted in this study, first contact access to PCPs and their expertise have been identified as issues elsewhere. 7,15 Transport came through as a major barrier to care in this study, but was not mentioned in the systematic review.…”
Section: Barriers To Carementioning
confidence: 93%
“…The quality of care in PHC facilities is a reoccurring topic that attracts public attention and scrutiny, following strong evidence throughout the years that the health system should be more responsive (e.g. Bresick et al 2019aBresick et al , 2019bKelly et al 2019;Peltzer 2009;Peltzer -Phaswana-Mafuya 2012).…”
Section: Patient Experiences In South Africamentioning
confidence: 99%